2022
DOI: 10.1002/smll.202205593
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving Grain Boundaries in 2D Materials

Abstract: provides a feasible pathway to achieving improved ductility for brittle alloys and ceramics. [9][10][11][12][13] Moreover, GBs prove to be capable of improving the minority carrier collection in polycrystalline CdTe and Cu(In,Ga)Se 2 solar cells, leading to higher efficiencies than their single-crystal counterparts by 24% and 69%, respectively. [14,15] The GB effects tend to be enhanced in 2D materials, owing to unique space dimensionality and reduced Coulomb screening. In that case, GBs can not only directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 169 publications
0
5
0
Order By: Relevance
“…This separates the two localized states and lessens the likelihood of a barrier forming between them 34 . Furthermore, the increase in charge carriers brought on by FeVO 4 that caused the coalescence of grain boundaries is responsible for this improvement in conductivity 36 . Compared to the PU/PMMA mixture, FeVO 4 ‐PU/PMMA nanocomposites have better conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This separates the two localized states and lessens the likelihood of a barrier forming between them 34 . Furthermore, the increase in charge carriers brought on by FeVO 4 that caused the coalescence of grain boundaries is responsible for this improvement in conductivity 36 . Compared to the PU/PMMA mixture, FeVO 4 ‐PU/PMMA nanocomposites have better conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…34 Furthermore, the increase in charge carriers brought on by FeVO 4 that caused the coalescence of grain boundaries is responsible for this improvement in conductivity. 36 Compared to the PU/PMMA mixture, FeVO 4 -PU/PMMA nanocomposites have better conductivity. The inclusion of nanomaterials gives systematic organization of NPs in the polymeric matrix, as seen by the XRD and ultraviolet-visible data.…”
Section: Conductivitymentioning
confidence: 97%
“…[31,32] Notably, GBs are pervasively in 2D materials due to the coalescence of randomly distributed grains with different crystallographic orientations. [33] Therefore, the design of a 2D ultrathin structure, which combines the coordination unsaturated amorphous phase with a highly conductive crystalline phase, together with the tailored M─O bonds, is a promising structure for greatly boosting the acidic OER kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 More importantly, it is reported that the failure mechanisms of 2D materials are dominated by grain boundary and thermal cracking. 17 The dissociation of H 2 O is energetically favorable along the grain boundaries, and the interaction between O* and B leads to the accumulation of O atoms, which accelerates the formation of Cu oxide/hydroxide. In this context, continuous h-BN layers with large grain sizes and minimal defects are highly required for better anticorrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, h-BN is considered to be a promising substitution for graphene as an anticorrosion layer . However, its application is largely limited by the fact that the large-scale growth of 2D h-BN has still not been achieved. , More importantly, it is reported that the failure mechanisms of 2D materials are dominated by grain boundary and thermal cracking . The dissociation of H 2 O is energetically favorable along the grain boundaries, and the interaction between O* and B leads to the accumulation of O atoms, which accelerates the formation of Cu oxide/hydroxide.…”
Section: Introductionmentioning
confidence: 99%